Analisis pengaruh XBRL terhadap kinerja perusahaan di India - Farisan Wanaputra; Siti Nurwahyuningsih Harahap (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to analyze the effect of XBRL adoption on firm performance, in terms of Return on Assets (ROA) as an accounting performance measurement and Market to Book Ratio (MTB) as the market performance measurement. The sample consists of 100 firms listed in National Stock Exchange (NSE) and Bombay Stock Exchange (BSE) from 2008 to 2013 that are selected using purposive sampling method. This research empirically tests the hypothesis using Ordinary Least Square (OLS). The findings show that XBRL adoption positively affects firm performance. Increasing information transparency due to XBRL adoption motivates firms to increase the quality of their financial reporting and performance. These results suggest that capital market regulators promote the benefits of XBRL adoption so that listed firms are highly motivated to adopt XBRL.